Використання цифрового радіометра на базі декаметрового радіотелескопа УРАН-3 для спостереження Сонця - Кошовий, В.В.; Лозинський, А.Б.; Івантишин, О.Л.; Харченко, Б.С.; Лозинський, Р.А. (Фізико-механічний інститут ім. Г.В. Карпенка НАН України, 2010)
The results of observations of the solar eclipse on 1, August 2008 using digital radiometer on basis the decameter radio telescope URAN-3 are presented. The observations were performed using a technique of scanning the passing source by a fixed beam pattern of antenna. In culmination for the coordinates of the radio telescope URAN-3 obscuration of the Sun at optical wavelengths was 11,5%. Relations of integral flux of the Sun masked by the Moon to not masked has been obtained.